The Impact of Cellular Therapies on Gastrointestinal Diseases: Applications and Challenges - Zhang, Meng-Meng; Hu, Yan; Xu, Jing; Liu, Ling; Lv, Lu-Lu (Turkish Journal of Gastroenterology, 2023)
Gastrointestinal diseases are highly prevalent, and their burden significantly impacts the quality of life of affected individuals. Inflammatory and immune-mediated intestinal diseases usually have a chronic course without adequate therapeutic modalities. Although much has been reported to comprehend these diseases, many remain resistant and refractory to conventional treatment approaches. Therefore, recent approaches to cellular therapy using stem cells, like hematopoietic stem cells and mesenchymal stem cells, and other cellular immunosuppressive modalities, like T-regulatory cells, were introduced and investigated in treating gastrointestinal diseases. We aimed to conduct a literature review to discuss the applications and challenges of cellular therapeutics in gastrointestinal diseases. Evidence from published clinical trials supports the safety and efficacy of cellular treatment in different immune-mediated and inflammatory gastrointestinal diseases. They can offer a longer duration of remission, being able to adjust the dysregulated immune system. However, there are various challenges to be considered by future trials, including the limitations of current clinical trials, challenges in retrieval and application of these therapeutics, and their mutagenesis potential. Cite this article as: Zhang M, Hu Y, Xu J, Liu L, Lv L. The impact of cellular therapies on gastrointestinal diseases: Applications and challenges. Turk J Gastroenterol. 2023;34(8):782-794.